Pengaruh Manajemen Laba Terhadap Kinerja Keuangan (Pada Perusahaan Sub Sektor Industry Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Jamilah, Jamilah; Septiana, Nani (Universitas Muhammadiyah Metro, 2022)
The results of this study indicate that earnings management has a significant effect on return on assets. It can be seen from the tcount value of 2.436 and t table 2.179, which means that t count is greater than t table. So it can be explained that profit management in the food and beverage industry sub-sector companies listed on the IDX in 2017-2019 has a significant effect on financial performance. Where earnings management describes the effect or effect of cash income and expenditures to ensure that the business generates net operating income.Keywords: Earnings Management, Financial Performance, Return On Assets (ROA)